Acute Oxalate Nephropathy following Ingestion of Averrhoa bilimbi Juice - Sreeja Nair; Jacob George; Sajeev Kumar; Noble Gracious (Case Reports in Nephrology)
Plant toxins are known to cause acute kidney injury in tropical countries. We report two cases of acute kidney injury with tubular oxalate deposition following ingestion of Averrhoa bilimbi fruit juice. Both patients had complete renal recovery though one required dialytic support.